Development of a wearable ultrasound–FES integrated rehabilitation and motor-functional reconstruction system for post-stroke patients - Cao, Yudong; Lu, Yun; Wang, Wenpan; Xu, Peng; Yang, Xiaoli; Zhang, Shiwu; Wu, Ming; Gong, Xinglong; Sun, Shuaishuai (Biomedical signal processing and control, 2025)
Post-stroke patients experience a significant decrease of self-care capabilities in their daily lives because of motor dysfunction. The combination of intention recognition and functional electrical stimulation (FES) is used frequently to assist in improving the self-care capabilities for post-stroke patients. However, the electrical noise from the environment and the weak bio-signal from post-stroke patients lead to low-accurate intention recognition for post-stroke patients. To overcome the issue, this paper introduces a wearable rehabilitation and motor-functional reconstruction system for post-stroke rehabilitation with a new intention recognition system. This system consists of an FES unit and a wearable musculoskeletal ultrasound system. The integration of the wearable ultrasound system allows for high-accuracy continuous intention recognition whilst the FES unit is in operation. This key feature significantly enhances the system’s robustness in FES control, augments the signal-to-noise ratio and offers precise assistance in the reconstruction of motor function, thereby improving the effectiveness of post-stroke rehabilitation. In this study, the feasibility and efficiency of the proposed system were investigated. In the clinical trial, eight post-stroke subjects were recruited. In the experiment of motor-functional reconstruction, the proposed system demonstrated enhancements of approximately 23 % and 76 % in wrist raising angle and velocity, respectively. These results demonstrated that the proposed wearable system is effective for active rehabilitation and potential candidate to reconstruct the motor function of post-stroke patients.